ASMA NADIA's NOVEL SAKINAH BERSAMAMU APPRECIATION IN DISCUSSION CONTEXT STUDY - Annim Hasibuan (Bajang Institute, 2022)
The problem in this study is what is the context of the discourse contained in the novel Sakinah Bersamamu by Asma Nadia?. The purpose of this research is to describe the context of discourse in Asma Nadia's Sakinah Bersamamu novel. This research is focused on analyzing the discourse context in Asma Nadia's Sakinah Bersamamu novel. The population in this study is the novel